Impact of social awareness, case detection, and hospital capacity on dengue eradication in Jakarta: A mathematical model approach - Dipo Aldila, ,- (Elsevier, 2022)
Fumigation is the most popular form of intervention in various parts of the world to combat the spread of dengue fever, including in the city of Jakarta, Indonesia. Various forms of intervention, such as media campaign and case detection, are being carried out to control dengue in Jakarta. This study aims to understand the impact of the media campaign and case detection in controlling dengue spread in the city of Jakarta via a novel mathematical model. The intervention of a media campaign can improve people’s knowledge of dengue, which can make them aware of dengue. Furthermore, we also define our recovery rate as a decreasing function depending on the number of hospitalized individuals. The model was developed as a novel SAEIHR-VW (Susceptible Aware Exposed Infected Hospitalized Recovered - Susceptible and Infected Mosquito) model. Incidence data in Jakarta during 2020 is used to estimate the best-fit parameter of the model. The analysis shows that the disease-free equilibrium is locally asymptotically stable when the basic reproduction number is less than one. The elasticity analysis demonstrates that media campaign intervention is much more sensitive than case detection in suppressing the basic reproduction number. Furthermore, larger case detection does not always provide a better result in reducing the basic reproduction number owing to the quality of treatment in the hospital. The dynamical system sensitivity analysis (local and global) shows that the infection probability rate is the most significant parameter for the infected and hospitalized individuals.